Plants and Phytochemicals for Peptic Ulcer: An Overview - Sen, Saikat; Chakraborty, Raja; De, Biplab; Mazumder, Joydeep (Pharmacognosy Reviews)
World is rich in medical lore. Plants are the basis of life on earth and are central to people's livelihoods. The use of plants in religious ceremonies as well as for magic and medicinal purposes is very commonplace and widespread. Plants and phytoconstituents are better choice to treat diseases than the allopathic drugs. Most of the drugs used in primitive medicine were originated from plants and are the earliest and principal natural source of medicines. The drugs from plants are fairly innocuous and relatively free from toxic effects. The nature has provided us various medicinal plants which became the storehouse of remedies to cure all ailments of mankind. In modern era many plant-derived compounds have been used as drugs, either in their original or semi-synthetic form. Peptic ulcer is widespread and common health problem now a day. Generation of free radicals, decrease in mucosal defensive factor or increase in mucosal injurious factor causes peptic ulcer. In this review attempts have been made to know about some plants and their constituents which may be used in treatment or prevention of peptic ulcer. Various plants like Anogeissus latifolia, Alchornea castaneaefolia, Utleria salicifolia, Solanum nigrum, Ocimum sanctum, Asparagus racemosus, Scoparia dulcis, Byrsonima crassa etc. and their phyto-constituents proved active in antiulcer therapy.
Keywords: Plants; Phytoconstituents; Peptic ulcer; Antioxidants; Cytoprotective